Theorizing as a Liberatory Practice? The Emancipatory Promise of Knowledge Co‐Creation With (Forced) Migrants - Halleh Ghorashi; Maria Charlotte Rast (Social Inclusion)
This thematic issue consists of empirical and theoretical contributions from South Africa, the United States, and the Netherlands that address how academic theorizing is co‐created by and co‐creates processes of emancipation and transformation for differently positioned and impacted individuals and collectivities. We invited knowledge co‐creators (both inside and outside academia) aiming to improve social inclusion and justice for refugees/forced migrants to engage with the question of how theory and practice are co‐created as an engaged, collaborative, reflective, and critical act between scholars and social movements, activists, artists, societal partners, and other individuals or communities. The contributions in this thematic issue highlight (1) how transformative co‐creation allows for a plurality of perspectives, stories, and experiences to be acknowledged in the creation of knowledge and solutions, (2) how the creation of more diverse, inclusive, and transformative knowledge and solutions challenges exclusionary, reductive or singular notions about refugees/forced migrants, and (3) what the conditions are for transformative co‐creation.